Partisipasi Masyarakat Dalam Proses Pembangunan Pelabuhan Kijing Kabupaten Mempawah - Aswa, Jumratul; Mardhalena, Azrita; Rasidar, Rasidar (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aimed to determine the interaction of the community with the village government and PT Pelindo and determined community participation in decision making. The problem of this research was that there were some people who did not attend meetings or discussions in decision-making deliberations and there were some people who refused land acquisition in the Kijing Port development process in Sungai Kunyit Laut Village of Mempawah Regency. The method used in this research is descriptive research method with qualitative analysis techniques. The theory used by the researcher in this study is the theory proposed by Cohen and Uphoff (in Dwiningrum, 2011: 61-62) which has 4 participating forms, such as: 1) Attendance at meetings is stated low which is influenced by the time of the meeting which coincides with working time for the community and the uninformed community about the meeting information. 2) Discussion, the community still defended their rights and only some of the community were present. 3) Contribution of thoughts, the community showed that they rejected the port development process. 4) The response or rejection of the program offered, the absence of definite clarity or clear details regarding the costs of the land acquisition process..Keywords: Community Participation; Kijing Port Development; Decision Making;                                           Mempawah Regency